Risk of dementia or cognitive impairment in non-alcoholic fatty liver disease: A systematic review and meta-analysis - Wang, Luping; Sang, Bowen; Zheng, Zuyan (Frontiers in Aging Neuroscience, 2022)
Objectives: To investigate whether Non-alcoholic Fatty Liver Disease (NAFLD) increases the risk of dementia or cognitive impairment. Methods: PubMed, EMBASE, Cochrane Library and Web of Science were systematically searched from their inception to 22 May 2022. Statistical analysis of nonalcoholic fatty liver disease and risk of cognitive impairment or dementia extracted from each article was performed using Stata software (version 16.0). The quality of this study was assessed using the Newcastle-Ottawa Quality Assessment Scale (NOS) and American Agency for Health Care Quality and Research's (AHRQ) cross-sectional study quality evaluation items. The funnel plots and Egger's test were used to assess publication bias. Results: We included 7 studies covering 891,562 individuals from 6 countries, which were published between 2020 and 2022. The pooling analysis shows that a history of NAFLD is associated with cognitive impairment (OR=1.44; 95% CI: 1.17-1.78; I2=0%, P=0.976). The history of NAFLD was not associated with an increased risk of all-cause dementia (OR=1.03; 95% CI: 0.97-1.09; I2=84.7%, P=0.000) and Alzheimer’s disease (OR=0.95; 95% CI: 0.83-1.09; I2=61.0%, P=0.077). Nonetheless, NAFLD was an obvious reduction of the risk of vascular dementia (OR=0.88; 95% CI: 0.79-0.98; I2=0.0%, P=0.768). In the subgroup analysis, both sexes of NAFLD have no different risk of dementia or cognitive impairment. The risk of dementia or cognitive impairment in the cross-sectional study (OR=1.49; 95% CI: 1.19-1.88; I2=0.0%, P=0.474) was slightly higher than in the retrospective cohort (OR=1.03; 95% CI: 0.97-1.09; I2=84.3%; P=0.000). Conclusions: NAFLD is associated with an increased risk of cognitive impairment and decreased the risk of vascular dementia. More studies are still needed to clarify the pathophysiological mechanism between NAFLD and dementia or cognitive impairment.